Increasing the Critical Power of Students to Overcome Fake News to Digital Age through the Science of Hadith Narration - Jundan, J; Aryani, Sekar Ayu; Nurgiyatna, N (Universitas Muhammadiyah Surakarta, 2022)
Purpose: The spread of fake news in digital media is very difficult to contain. Fake news has the capacity to wreak havoc on society. Fake news has gained ground in the field of hadith narration. So that a great deal of fake information is disseminated as if it were the truth. Through the science of hadith transmission, the objective is to strengthen students' ability to discern fake information in the digital age.Methodology: This research utilizes a qualitative, descriptive approach. Interview, observation, and document-derived data. The research technique utilizes purposive sampling, whereas the validity test uses the triangulation method.Results: In conclusion, fake news can be recognized by news content which is inconsistent with common reality, is excessively provocative, and makes readers intrigued and concerned. The news is rarely absorbed in accordance with the logic of common sense and content which provokes hatred. The method for preventing fake news is to; 1). Be wary of topics that defy common sense reasoning, are controversial, and breach conventional guidelines. 2). Identifying fake news producers and warning others to avoid them. 3). Analyze the conduct and personal histories of news anchors, as well as their websites, to obtain additional details about them. 4). Do not quickly spread fake information. 5). Compile a database of the sources of fake information circulating in the community and track the studies of hoax news observers.